O ensino na educação básica na comunidade quilombola de Helvecia/Bahia - Krull, Wellington Ferreira (2019)
The focus of the research is "Teaching in Basic Education in the Quilombola Community of Helvécia, Bahia", in the environment of the "João Martins Peixoto Municipal Public School", located in the urban area of Quilombo de Helvécia, in the municipality of Nova Viçosa, Bahia, seeks to understand how education is being developed in the basic education of the quilombolas, based on the analyzes carried out in the Pedagogical Political Project and the Curriculum adopted by the school. However, before we arrived at the analyzes, it became necessary to demonstrate the historical factors, from the founding of the Leopoldine Colony to its present form of the Quilombola Community of Helvécia, also carrying out studies on the public policies and the education directed to the quilombolas, mainly with the Law of Guidelines and Bases of Basic Education Quilombola. In the methodology proposed for this study, we used the qualitative approach with explanatory analyzes, along with bibliographical, documentary and field research, as well as free observation, interviews, questionnaires with EPM students "João Martins Peixoto", all of this to produce the presented data and to reach the answers of the objectives. Linked to these sources of research, the present study was anchored in the theoretical conceptions of Freire (1987, 1992, 2006), Sacristán (2000), Moreira e Silva (2002), Gomes (2012), among other scholars of the subject. Following the objectives of the research, it was possible to make a systematic study of the quilombo and to reflect on its basic education and its contribution in the permanence and valorization of the historical-cultural aspects and, finally, to conclude that the basic education developed in the Quilombola Community of Helvécia presents a Political Pedagogical Project outdated by the current situation of the school, modified with the construction of some school units in the neighborhood of the quilombo. Regarding the curriculum, we observe that the school follows the curriculum prescribed by the education system of the State of Bahia by imposition of the educational system of the Municipality of Nova Viçosa. In the final conclusions, we were able to bring the answers to the questions raised and the objectives proposals, contributing to the need to create a specific curriculum for the Helvetian Quilombola Community, in addition to the present research to awaken other studies on the theme.